Association between psychological resilience and body mass index in a community‐based population: A cross‐sectional study - Nan Zheng; Mansi Zhuang; Yanan Zhu; Yu Wang; Meijie Ye; Yasi Zhang; Yiqiang Zhan (Wiley, 2024)
Abstract Background and Objective While earlier studies have focused on the relationship between stress and obesity, there was a gap in understanding the potential impact of positive psychological factors, such as resilience, on obesity. By investigating the role of psychological resilience with obesity, this study aimed to address this gap and tackle obesity through a positive psychological framework. Methods Participants consisted of 2445 community residents from Shenzhen, China, with a mean age of 41.09 ± 13.72 years, comprising 846 males and 1599 females. Psychological resilience was measured using the Brief Resilience Scale; gender, age, marital status, education level, smoking status, alcohol consumption, frequency of physical exercise, and perceived stress were considered potential confounding factors. The relationship between psychological resilience and body mass index (BMI) was examined through multiple linear regression and logistic regression analyses. Results The participants had an average psychological resilience score of 3.46 (standard deviation [SD] = 0.62) and an average BMI of 22.59 (SD = 3.35), with 104 individuals (4.3%) identified with obesity. In the fully adjusted multiple linear regression model, a higher psychological resilience score was associated with a higher BMI (β = 0.507, 95% CI:0.283, 0.731). In the logistic regression model, higher psychological resilience scores were linked to increased obesity risk, with a more significant association observed among males (odds ratio [OR] = 2.169, 95% CI:1.155, 4.073), while psychological resilience acted as a protective factor against underweight among females (OR = 0.528, 95% CI:0.376, 0.816). Conclusion The study demonstrated a significant link between higher psychological resilience and elevated BMI, emphasizing the complex relationship between psychological fortitude and weight management. Interventions targeting socioeconomic status, education, lifestyle habits, and physiological well‐being might offer a promising strategy for enhancing psychological resilience and promoting healthier weight. Emphasizing self‐efficacy and coping skills at the individual level could contribute to balanced weight and comprehensive health outcomes, addressing the global challenge of obesity.